Construção civil sustentável: avaliação da aplicação do modelo de gerenciamento de resíduos da construção civil do SINDUSCON-MG em um canteiro de obras: um estudo de caso - Alair Goncalves Couto Neto (2007)
The discarded materials left by the civil construction in cities, become real deposits of raw material. They are not used and cause a lot of damage in the inhabitants quality of life. The perception of the need to expand the concept of basic sanitation to environmental sanitation,dealt in an integrated way with the various components (water, sewer, solid waste, drainage and vectors control) that influence the urban environment, has been happening recently only. Only with the implementation of the Determination CONAMA n. 307 (from July 5th, 2002), the National Environmental Council established guidelines, criteria, and procedures to the management of civil construction waste. In Brazil, some town halls, trying to solve the civil construction waste issue are starting to recycle it in appropriate mills built for this purpose.With the purpose of civil construction waste management at the working site, the SINDUSCON-MG developed a leaflet of Civil Construction Waist Management. It was created to follow the Determination CONAMA n. 307/2002 and minimize the environmental impacts in the productivity of the building industry. Through the project plan, it maximizes the use of materials, the segregation to cut the builders costs, the recyclable waste removal (cardboard, glass, plastic) and the final disposition, that directs to the embankment only the materials which cant be recycled. The adequate management of the waste produced by the companies, including its reduction, reuse and recycling, will make the constructive process more profitable and competitive and above all, healthier. The aim of this current work is to analyze the programs performance of working site waste management, evaluating the acquired results with its implantation and comparing these results with other authorsreferences and from the building company itself. This evaluation will be of great importance due to the fact that the civil construction industry is responsible for approximately half the trash generated by Brazilian cities. The success of this model can really reduce the amount of waste generated and discarded by the civil construction industry. The results achieved demonstrate the efficiency of the program which, besides selecting residues, reduced significantly the generated volume. The work's residues generation index is 0,089 m3 for each construction m2, staying inside the established limit proposed, thus serving as reference for the next works of the company and all the sector of civil construction.